Implementasi Metode Rote Learning dalam Pembelajaran Tahfidz Al-Quran di Pondok Pesantren Hidayatul Mubtadiin Tlogomojo Rembang - Muhammad Bahauddin Haidar (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2025)
This study aims to analyze the implementation of the rote learning method in qur’an memorization (tahfidz) at Pondok Pesantren Hidayatul Mubtadiin Tlogomojo, Rembang. The research focuses on four main aspects: planning, implementation, effectiveness, and evaluation. A qualitative approach with an ethnomethodological perspective was employed, using observation, interviews, and documentation as data collection techniques. The findings indicate that, at the planning stage, students are guided to memorize gradually through continuous repetition, understanding of meaning, and daily memorization submissions. During implementation, tahfidz activities are carried out from morning to afternoon through a combination of muroja’ah, collective prayers, and daily recitations. The method proves effective in strengthening long-term memory and achieving memorization targets, although several obstacles remain, including lack of discipline, weak time management, and emotional factors that affect students’ motivation. Evaluation is conducted at multiple levels, consisting of daily submissions, weekly assessments, and memorization examinations for students who have completed 30 chapters, along with continuous guidance for alumni to maintain their memorization. Overall, the application of rote learning contributes significantly to the success of the tahfidz program, supported by internal factors such as student consistency and external factors including guidance from mentors and a supportive pesantren environment. Nevertheless, challenges related to discipline and emotional conditions must be addressed to further enhance the effectiveness of this method.